Assessing the economic feasibility of cattle farm agritourism at ex-coal mine lands through the partnership program (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Mukarrom F, Gravitiani E, Pranoto P, Karsidi R. 2022. Assessing the economic feasibility of cattle farm agritourism at ex-coal mine lands through the partnership program. Biodiversitas 23: 1843-1851. Extensive coal mining activities have various negative impacts on environment as well as on local communities living adjacent to the mining areas. Reclamation followed by revegetation using forage crops could significantly improve the value of the land. The forage crops produced from the reclaimed land can be integrated with developing cattle farm agritourism to obtain a win-win solution of environmental recovery by enhancing the socio-economic livelihood of local communities. Hence, this study aims to analyze the economic feasibility of developing cattle beef agritourism at ex-coal mine lands in South Sumatra, Indonesia, and assess its potential in increasing the effectiveness of partnership program funding. The analysis of feasibility criteria revealed a Net Present Value (NPV) of 129,152,169,746 IDR, meaning that the project is feasible to be implemented since the NPV is greater than 1. The Benefit-Cost Ratio (BCR) was 1.22, which is more than 1, implying that it is feasible to be run. The Payback Period (PP) was 3.5 years which is far shorter than the estimated investment period of 15 years. The Internal Rate of Return (IRR) was 35.6% which is much greater than the assumed annual interest rate of 8%. The farmers’ plasma system analysis showed that the cattle farm agritourism could increase the amount of fund distribution, collectibility rate, and also farmer’s income.
Keywords: Biodiversity, community development, cow farm tourism, ex-mining area utilization